PENGGUNAAN SILASE BIOMASSA TANAMAN UBI KAYU (KULIT UMBI, BATANG, DAN DAUN) SEBAGAI PAKAN KAMBING PERANAKAN ETAWAH (PE) - Kiston Simanihuruk; Juniar Sirait; Muhammad Syawal (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Cassava biomass (bark tubers, stems and leaves) is quite potential and need to be explored as feed component for goats. The research was carried out to determine the effect of cassava biomass silage as feed supplementation for growth of male Etawah crossbred post weaning. The experiment was using a completely randomized design (CRD) for 30 (thirty) male Etawah crossbreds post weaning (11-14 kg live weight). Technology of silage biomass cassava plant used 12% additives molasses. The feed treatment consists of: P0 = without giving silage biomass cassava plant, P1=750g/head/day of cassava biomass silage, and P2=1000 g/head/day of cassava biomass silage. These cassava silages were given to Etawah crossbred in the morning. The result showed that the chemical and physical characteristics of cassava silage biomass plant which was using 12% of molasses additives could be categorized significant. Statistical analysis showed that feeding silage crop cassava gave significant effect (P<0.05) to growth of male Etawah crossbred post weaning. The highest average growth was P2 = 53.71g/head /day. It can be concluded that silage technology could increase the period of saving cassava biomass and improved growth of countryside goats.